1978
DOI: 10.1152/ajpheart.1978.235.1.h40
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal muscle and mucosal blood flow during direct sympathetic stimulation

Abstract: The effect of direct sympathetic stimulation on intestinal muscle and submucosal-mucosal vasculatures was studied in the anesthetized rat. Blood flow was calculated from direct measurements of vessel diameter and red cell velocity. Stimulation at 4 Hz caused a slight reduction (4%) in muscle flow, but had no measurable effect on submucosal-mucosal flow; stimulation at 8 and 16 Hz caused muscle flow to decrease to 58.3 +/- 8.7% (SE) and 31 +/- 5.1%, respectively, of control flow, and mucosal flow, to 73 +/- 3.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…In a previous study, we found that the widespread arterial and arteriolar constriction induced by nerve stimulation at 3,8 or 16 Hz is sufficient to significantly increase vascular resistance in this segment of the intestine, as evidenced by frequencydependent reductions in blood flow through the small artery supplying this portion of the network [7], These find ings are consistent with an earlier study on the rat intestine demonstrating that direct symapthetic stimulation at 8 and 16 Hz caused frequency-dependent reductions in blood flow through submucosal arterioles [ 17],…”
Section: Effect O F Sympathetic Nerve Stimulation On Resistance Vesselssupporting
confidence: 91%
See 1 more Smart Citation
“…In a previous study, we found that the widespread arterial and arteriolar constriction induced by nerve stimulation at 3,8 or 16 Hz is sufficient to significantly increase vascular resistance in this segment of the intestine, as evidenced by frequencydependent reductions in blood flow through the small artery supplying this portion of the network [7], These find ings are consistent with an earlier study on the rat intestine demonstrating that direct symapthetic stimulation at 8 and 16 Hz caused frequency-dependent reductions in blood flow through submucosal arterioles [ 17],…”
Section: Effect O F Sympathetic Nerve Stimulation On Resistance Vesselssupporting
confidence: 91%
“…Mor ris Plains, N.J., USA) were added to the superfusate to suppress intestinal motility. At these concentrations, isoproteronol and phe nytoin have no adverse effects on arteriolar tone in this vascular bed [17], After exteriorization of the ileum, two small incisions 6 cm apart were made by thermal cautery along the antimesenteric border and chyme was flushed from the lumen through these incisions. Four sutures were then tied to the antimesenteric border at 1-cm intervals and the bowel was draped over a transparent pedestal.…”
Section: Surgical Preparation O F the Small Intestinementioning
confidence: 99%
“…Isoproterenol (10 mg/l; Sigma, St. Louis, Mo., USA) and phenytoin (20 mg/l; Parke-Davis, Morris Plains, N.J., USA) were added to the superfusate to suppress intestinal motility. At these concentrations, neither agent alters resting arteriolar tone in this vascular bed [14]. With most of the preparation covered by polyvinyl film, and superfusate flow directed beneath the film, solution PO 2 above the tissue is maintained at 40–50 mm Hg under normal conditions [15].…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies in cat and dog small intestine have shown that variation of the total blood flow rate is accompanied by different changes of the flow rate in the layers of the intestinal wall (9, 4 8 -6 1 ) (see next section). In the rat small intestine stimulation of sympathetic nerve fibers reduces total blood flow rate by 50%, but the fraction supplying the mucosal-submucosal layers increases from 60 to 72% (47). An increase in resistance of the first barrier would also decrease the absorption rate, for example by an increase of the unstirred layer thickness evoked by continuous secretion of mucus.…”
Section: Influence Of Direction Of Blood Flow Change On Intestinal Abmentioning
confidence: 99%
“…From the experimental data obtained in rat jejunum (10,(12)(13)(14) the frac tion of the 'absorption site' blood flow has been calculated as 10 -40%. However, the mucosal blood flow rate in rat small intestine amounts to 60-70% (47,(70)(71)(72). In dog small intestine, the 'absorption site' blood flow rate represents about 5% of the total blood flow rate (40, 42) calculated from the absorption rate of tritiated water, while according to microsphere measurements the fraction of mucosal blood flow is 65-70% (54,73).…”
Section: Influence Of Blood Flow Pattern In Intestinal Wall On Intestmentioning
confidence: 99%